1995
DOI: 10.1016/0014-5793(95)00196-g
|View full text |Cite
|
Sign up to set email alerts
|

The active site of the cyanide‐resistant oxidase from plant mitochondria contains a binuclear iron center

Abstract: The cyanide-resistant, alternative oxidase of plant mitochondria catalyzes the four-electron reduction of oxygen to water, but the nature of the catalytic center associated with this oxidase has yet to be elucidated. We have identified conserved amino acids, including two copies of the iron-binding motif GIu-X-X-His, in the carboxy-terminal hydrophilic domain of the alternative oxidase that suggest the presence of a hydroxo-bridged binuclear iron center, analogous to that found in the enzyme methane monooxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
96
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 27 publications
4
96
1
Order By: Relevance
“…This result has major implications as to the plausibility of the two structural models. Siedow et al (5,6) implicitly suggested that Glu-217 would be located at the cytoplasmic side of the inner mitochondrial membrane. Since both reduction of oxygen and oxidation of ubiquinol were proposed to occur toward the matrix side of the membrane, it is hard to envisage how Glu-217 would play a functional role in such a model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result has major implications as to the plausibility of the two structural models. Siedow et al (5,6) implicitly suggested that Glu-217 would be located at the cytoplasmic side of the inner mitochondrial membrane. Since both reduction of oxygen and oxidation of ubiquinol were proposed to occur toward the matrix side of the membrane, it is hard to envisage how Glu-217 would play a functional role in such a model.…”
Section: Discussionmentioning
confidence: 99%
“…Although this second model also classifies the AOX as a di-iron protein, it differs in the precise ligation sphere of the di-iron center (7). For instance, one of the C-terminal Glu-X-X-His motifs identified by Siedow et al (5,6), containing Glu-270, appeared not to be fully conserved in the newly identified sequences and consequently seemed unlikely to play a role in ligating iron. Instead, Andersson and Nordlund used a third Glu-X-X-His motif (that contains Glu-217, which is located in the intermembrane space according to the Siedow et al model) to coordinate the iron atoms.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Two (E 301 XXH 304 and E 356 XXH 359 in Fig. 2) of the three EXXH motifs conserved in M. grisea, N. crassa and all higher plant sequences have been suggested to be involved in forming the di-iron center of the enzyme (Siedow et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The study of these alternative dehydrogenases and several other aspects of the respiratory chain of A. angustifolia mitochondria are of great importance, especially the study of AOX, as this is a conserved protein along evolution because of its occurrence in fungi, protozoa and plants (Siedow et al, 1995). The Araucariaceae family has an ancient origin in the Triassic Period and the araucarians appear to have maintained a preference for subtropical or mesothermal conditions, illustrated by the present distribution of A. angustifolia in southern Brazil (Kershaw and Wagstaff, 2001).…”
Section: Discussionmentioning
confidence: 99%